Identification and Incident Rate of Phylum Protozoa Around The Sad and Grazing Fields of Madura Cattle in Sub-District of Geger Bangkalan District - Chikita Helvi Silvana Putri; Sarmanu Sarmanu; Lilik Maslachah (Universitas Airlangga, 2021)
This research aims to determine the percentage and kind of Phylum Protozoa contamination in around the sed and grazing field soil of Madura cattle in Sub-District of Geger, Bangkalan District. The research was conducted on March untul Mei 2019. The method of this research used a non-experimental method and through an observation study. The sample of this research was 100 samples of around the sed and grazing field soil, then examined in the laboratory of Parasitology Airlangga University, Division of Veterinary Parasitology used Sucrose Floatation Method. The result showed that percentage of Phylum Protozoa was 53%. Based on the type of soil, the highest contamination was Eimeria spp. (43%), followed by Blastocystis sp. (24%) and Isospora spp. (4%). Based on location, the percentage of grazing fields was higher (75%) than around the sad (38.3%). The results of statistical analysis using Chi-square test showed significant differences in the percentage between contamination around of the cages and grazing field soil (P<0.05).